REMOVAL AND LEACHING OF NUTRIENTS BY SALVIN1A MOLESTA MITCHEL AND EICHHORNIA CRASSIPES (MART.) SOLMS - Y.C. WEE and H.H. YEOH (Biotropia: The Southeast Asian Journal of Tropical Biology, 1989)
Profuse growth of Eichhornia crassipes and Salvinia molesta in Singapore reservoirs required their regular manual removal as their prolonged presence can lead to deterioration in the quality of the potable water. Clearing of the reservoir catchments, together with regular removal of the weeds and dumping them away from the catchments, should, in the long term, reduce their presence in the reservoirs. Laboratory experiments showing the removal of chloride, sulphate, phosphorus and nitrate from the growing medium and the release of chloride, phosphorus and nitrate by rotting plants should convince the administrators of the benefit of proper management of the problem.